Building innovative teams : - Harris, Chris (Palgrave Macmillan, 2003)
Innovation is critical for securing competitive advantage and achieving business success. Yet, for many organizations it remains elusive. This book shows how to build innovative teams who will deliver innovations capable of transforming performance. It includes the strategy of building innovative teams and the practical tools that will form part of this process.